Efisiensi Relatif Perguruan Tinggi Negeri Di Indonesia: Pendekatan Data Envelopment Analysis (DEA) - Ngatindriatun Ngatindriatun; Hertiana Ikasari (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2009)
The purpose of this paper is to analyze the relative efficiency of 25 Indonesian State Universities in the period of 2002 to 2006. The analysis used in this research was Data Envelopment Analysis (DEA) with the A.T Flegg, D.O Allen, K. Field and T.W. Thurlow’s model. The input variables used were the number of staff, the number of undergraduate students and the number of postgraduate students. The output variables used were the number of undergraduate alumni and the number of postgraduate alumni. The result was there were many Indonesian state Universities which is significantly efficient in the period of 2002 to 2006.